Innovation hesitancy: exploring reluctance to digital innovation in the Swedish cultural sector - Hanna Carlsson; Ahmad Kamal; Charlie Järpvall (Information Research: An International Electronic Journal)
Introduction. This paper explores a challenge for any novel digital intervention: the hesitancy or reluctance among the designated user group.